Study of the feasibility of adaptation of the business process sales and operations planning (S&OP) in a university hospital - Cardoso, Wagner (Journal of Innovation and Healthcare Management, 2019)
In this research, the author set out to answer the following research question: how to adapt the S&OP process to the hospital services sector and how to proceed with its implementation in this environment. Therefore, the research has as general objective to analyze and elaborate a proposal of adaptation of the S&OP to the sector of hospital services and to propose its implantation through a process described by a step-by-step and preliminary procedure in the scope of the university hospital object of the study, more specifically in the emergency care. To this end, the author described the steps and procedures of the S&OP implementation process and adapted them to the hospital services environment, with emphasis on aspects related to hospital management with regard to demand management by hospital, capacity management and level of service. In this case, it is important to emphasize that in addition to elaborating the procedure of the S&OP implantation process for the emergency care of the hospital unit object of the study, the development of the work emphasized the medical clinic specialty for the case study. This research was also aimed at reducing the scarcity of S&OP scientific bibliographic material applied to the health care sector.